Psychological implications in the coaching context: the mediating role of motivational intensity and team cohesion in elite sport performance - Javed, S.; Naseer, A.; Nawaz, A.; Naveed, Q.; Ullah Khan, I.; Gul, F.; Mohy ud Din, B. (Journal of Physical Education and Sport, 2020)
Purpose:The primary purpose of the existing research was to determine relationships of coaches, team cohesiveness, motivational intensity with players` performance of field hockey at national level. The secondary objective of the present study was to determine the regression effect on the performance of field hockey players and the role of mediators between independent construct and outcome variable.Material and Methods:The population (N-3207) was comprised of Pakistani national players of field hockey. The large sample size comprising 510 respondents was chosen for the purpose of data collection. Adapted and modified survey questionnaire with the permission of diverse original authors was employed as research instrument. Descriptive statistics, correlation analysis and multiple regression analysis were utilized to evaluate the collected data. Results:The findings revealed medium and significant association of hockey coaches with performance of national players. Results indicated that team cohesiveness had better and significant association with Pakistani players` performance. Findings revealed significant and medium association between motivational intensity and players` performance. The results of multiple regression analysis revealed that all constructs had significant effect on outcome variable. Findings to test the path model revealed that mediating constructs along with independent variable contributed significantly to the performance of national hockey players. Conclusion:It was overall concluded that the thrust of good coaching structure, excellent team collaboration, and high motivation intensity is still required to boost players` performance of Pakistani field hockey at its national level. The sport authorities,sports federations, sports associations, and sport institutions of the field hockey should take serious steps to uplift the past statures and glories of their national game.